The Decision to Admit for Threatened Preterm Birth [25K]. (May 2018) - Fisher, Lytia; Lewis, Dawnette; Waldron, Carolyn; Pan, Stephanie
Abstract : INTRODUCTION: Preterm labor (PTL) is the most common reason for antepartum hospital admission, yet only 10% of those presenting will deliver within 7 days, while 30% resolve spontaneously. The American College of Obstetricians and Gynecologists (ACOG) defines PTL as regular uterine contractions with change in cervical dilation and/or effacement, or regular contractions with cervical dilation of at least 2 cm. We hypothesized that the majority of patients admitted for PTL do not meet ACOG criteria and have lower prevalence of preterm birth. METHODS: This IRB-approved, retrospective chart review included all PTL admissions of singleton pregnancies less than 37 weeks gestation at Mount Sinai West from October 1, 2012 to October 1, 2016, excluding those with membrane rupture, pre-eclampsia, or abruption. Statistics included χ 2, Student t -test, and multivariable logistic regression. RESULTS: PTL admissions (n=179) were divided into those that met ACOG criteria on first admission (n=73) and those that did not (n=106). Patients who did not meet ACOG criteria had a much lower prevalence of preterm birth than those who did (40/92 [41.2%] versus 55/67 [82.1%]; P <.001), and the ACOG group was more likely to deliver on first admission (53/71 [74.7%] versus 19/104 [18.3%]; P <.001). Demographics were comparable between groups, except median gestational age at admission was higher for the ACOG group (35.1 [33.1–36.3] versus 30.77 [28.7–33.6]; P <.001). Adjusting for gestational age at admission, the association between meeting ACOG criteria and delivering on initial admission was OR 9.96 (95% CI 4.62–21.29; P <.001). CONCLUSION: ACOG criteria for PTL are frequently ignored when admitting patients. Stricter adherence could reduce unnecessary admissions and costs.